1990
DOI: 10.1136/jnnp.53.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Pathological stretch reflexes on the "good" side of hemiparetic patients.

Abstract: The reflex EMG responses from a tendon tap or an imposed, medium amplitude (300), stretch at a range of stretch velocities have been recorded from the triceps and biceps muscles of normal human subjects and in both the affected and "unaffected" arms of hemiparetic patients under relaxed conditions. In the hemiparetic arm, exaggerated tendon jerks were, as expected, observed in both muscles. The response of the biceps to elbow extension was also exaggerated compared with normal values and displayed both an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 12 publications
10
49
0
1
Order By: Relevance
“…The PHL showed some signs of perturbed motor control and was not absolutely ''normal''. In 10 hemiparetic patients, Thilmann et al [26] found increased EMG responses to stretch in the healthy triceps of hemiparetic patients, with shorter latency activity on the healthy side of hemiparetic subjects. The biceps presented a depression of the EMG response to stretch, with a decreased biceps tendon reflex (p < 0.001).…”
Section: Healthy Lower Limb Of Patientsmentioning
confidence: 99%
“…The PHL showed some signs of perturbed motor control and was not absolutely ''normal''. In 10 hemiparetic patients, Thilmann et al [26] found increased EMG responses to stretch in the healthy triceps of hemiparetic patients, with shorter latency activity on the healthy side of hemiparetic subjects. The biceps presented a depression of the EMG response to stretch, with a decreased biceps tendon reflex (p < 0.001).…”
Section: Healthy Lower Limb Of Patientsmentioning
confidence: 99%
“…In such a condition a displacement of the elbow joint is associated with an increased EMG activity in the stretched muscles of the spastic side compared to the una ected side in patients with spastic hemiparesis. 19,26 Nevertheless, subsequent studies analyzing the di erent components which contribute to muscle tone clearly revealed that muscle hypertonia is more associated with muscle ®bre contracture than with re¯ex hyperexcitability. 11,27 Studies on muscle tone and re¯ex activity have usually been performed under passive motor conditions.…”
Section: Clinical Spasticitymentioning
confidence: 99%
“…11,27 Studies on muscle tone and re¯ex activity have usually been performed under passive motor conditions. 26,28 In such a condition, increased elbow torque following a displacement was associated with an increased EMG activity in the¯exor muscles of the spastic side compared to the una ected side in patients with spastic hemiparesis. 19 Nevertheless, spastic muscle hypertonia was found to be closely associated with muscle ®bre contracture but not with re¯ex hyperexcitability.…”
Section: Clinical Spasticitymentioning
confidence: 99%
“…The experiment was performed on both paretic and nonparetic elbow joints. Although the nonparetic limb may sometimes have minor detectable impairments (Thilmann et al 1990), it was designated as a control for the impaired limb because it is not spastic and has similar musculo-tendon architecture and limb mass. However, to control for possible changes in the nonparetic side, we used healthy age-matched subjects as secondary or additional controls.…”
Section: Subjectsmentioning
confidence: 99%